2004
DOI: 10.1027/1618-3169.51.4.319
|View full text |Cite
|
Sign up to set email alerts
|

On Raising the International Dissemination of German Research

Abstract: It has been proposed that German basic psychology journals should change publication language to English in order to facilitate access to research from German-speaking countries. However, to truly increase the dissemination of German research, it seems crucial to progress towards an internationalization of authors and readers. We applied bibliometric analysis to investigate the impact of the transition to English on the rate of foreign authors publishing in Zeitschrift für Experimentelle Psychologie/Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 107 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…While researchers want to publish in international journals in English and promote their international influence (He & Spink, 2002; Sin, 2005), they also want to pursue regional research influence by disseminating regional research results to local readers who prefer their native languages (Li, 2014; Salager‐Meyer, 2014). Therefore, although switching to an English‐language journal has been discussed as a way of increasing journal impact internationally (Dinkel et al, 2004; Kirchik et al, 2012), it also has unfavourable consequences for local researchers, readers and research communities. To overcome language barriers, Steigerwald et al (2022) and Amano, Rios Rojas, et al (2021) suggested utilizing machine translation, which has become relatively reliable these days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While researchers want to publish in international journals in English and promote their international influence (He & Spink, 2002; Sin, 2005), they also want to pursue regional research influence by disseminating regional research results to local readers who prefer their native languages (Li, 2014; Salager‐Meyer, 2014). Therefore, although switching to an English‐language journal has been discussed as a way of increasing journal impact internationally (Dinkel et al, 2004; Kirchik et al, 2012), it also has unfavourable consequences for local researchers, readers and research communities. To overcome language barriers, Steigerwald et al (2022) and Amano, Rios Rojas, et al (2021) suggested utilizing machine translation, which has become relatively reliable these days.…”
Section: Discussionmentioning
confidence: 99%
“…Although having a common language can facilitate international scholarly communication (Montgomery, 2013), this has led to the assumption that significant scholarly communication takes place in English—an assumption that also applies to publications in English‐language international journals. As a result, international journals currently focus on research in the English‐speaking Western world, and non‐English‐language regional journals are perceived as qualitatively inferior to English‐language international journals (Dinkel et al, 2004; Kirchik et al, 2012). However, it has been widely acknowledged that regional journals from non‐English‐speaking countries (NESC) make unique and valuable contributions to global scholarly knowledge (Amano, Berdejo‐Espinola, et al, 2021; Amano, Rios Rojas, et al, 2021; Angulo et al, 2021; Khelifa et al, 2021; Márquez & Porras, 2020; Salager‐Meyer, 2014; Steigerwald et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One of these, is the language of publication of the journals; the dominance of English in biomedical publications has well been consolidated [11]. It is possible, therefore, that editorial committees of European journals published in local languages have been tempted over the last years to change the language of publication into English, so as to increase the penetration of the journals in the global scientific community [12]. The latter could have led into a rise of their impact factor.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists want to increase their number of citations (Furnham, 2020), and this forces them to publish in English and not in their native language (López-Navarro et al, 2015). Journals have a similar motivation (Chavarro et al, 2018), so they follow the same pattern, abandoning local languages and publishing in English (Dinkel et al, 2004). For an increased citation rate, it is also beneficial to get co-authors from developed countries (Meneghini et al, 2008) and publish in journals in these countries (Strehl et al, 2016).…”
mentioning
confidence: 99%